Prevalence of netB-positive Clostridium perfringens in Italian poultry flocks by environmental sampling. (March 2020) - Profeta, Francesca; Di Francesco, Cristina E.; Di Provvido, Andrea; Scacchia, Massimo; Alessiani, Alessandra; Di Giannatale, Elisabetta; Marruchella, Giuseppe; Orsini, Massimiliano; Toscani, Tonino; Marsilio, Fulvio
Clostridium perfringens type G is one of the pathogens involved in enteric diseases in poultry. NetB, a pore-forming toxin, is considered the main virulence factor responsible for necrotic enteritis during C. perfringens infection. We carried out a field study involving 14 farms to evaluate the occurrence of netB- positive C. perfringens and the impact of infection in Italian poultry flocks. Environmental samples ( n = 117) and 50 carcasses were screened by microbiologic and molecular methods. Microbiologic investigations yielded 82 C. perfringens isolates. DNA was extracted from all samples and screened for α-toxin and NetB encoding genes by real-time PCR. The C. perfringens α-toxin gene was detected in 151 of 167 extracts (90.4%), and 31 of 151 (20.5%) were netB gene positive also. Sixteen isolates from a turkey flock with mild enteric disorders were also netB positive, demonstrating their occurrence not only in broiler but also in turkey flocks. A pulsed-field gel electrophoresis protocol was optimized to evaluate the diversity among isolates and revealed high genetic heterogeneity. The complete NetB toxin-coding gene of 2 C. perfringens isolates from turkey and broiler flocks were analyzed and showed very high relatedness with analogous sequences worldwide.